2013
DOI: 10.1155/2013/183024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria from Mature Oocyte to Viable Blastocyst

Abstract: The oocyte requires a vast supply of energy after fertilization to support critical events such as spindle formation, chromatid separation, and cell division. Until blastocyst implantation, the developing zygote is dependent on the existing pool of mitochondria. That pool size within each cell decreases with each cell division. Mitochondria obtained from oocytes of women of advanced reproductive age harbor DNA deletions and nucleotide variations that impair function. The combination of lower number and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(137 citation statements)
references
References 121 publications
(157 reference statements)
1
136
0
Order By: Relevance
“…Although the outcome of IVF treatment may be improved by selecting euploid oocytes (Geraedts et al 2011), whether any interventions can be designed to rescue fertility in women who produce no euploid oocytes remains controversial. Procedures, such as oocyte cytoplasmic donation or mitochondrial augmentation of MII-arrested oocytes (Chappel 2013), have been proposed as a means of boosting fertility in older women. However, given the growing body of evidence that defects in centromeric cohesion are a major cause of aneuploidy in human oocytes from older women, it is difficult to envisage how interventions, such as mitochondrial augmentation, could prevent these from segregating randomly during anaphase II.…”
Section: Discussionmentioning
confidence: 99%
“…Although the outcome of IVF treatment may be improved by selecting euploid oocytes (Geraedts et al 2011), whether any interventions can be designed to rescue fertility in women who produce no euploid oocytes remains controversial. Procedures, such as oocyte cytoplasmic donation or mitochondrial augmentation of MII-arrested oocytes (Chappel 2013), have been proposed as a means of boosting fertility in older women. However, given the growing body of evidence that defects in centromeric cohesion are a major cause of aneuploidy in human oocytes from older women, it is difficult to envisage how interventions, such as mitochondrial augmentation, could prevent these from segregating randomly during anaphase II.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced pool of mtDNA within the oocyte has been associated with a reduced fertilization potential (276) and also a reduced ovarian reserve (213). Furthermore, ageing is associated with an adverse effect on the mitochondria [reviewed by Schatten (297)], leading to an in increase in mtDNA damage and mutations with mtDNA, structural abnormalities with the mitochondria, a reduction in ATP synthesis, and an increase in ROS production (57,297). Putative methods to improve mitochondrial function are the oral administration of CoQ10 (32), an electron transporter involved in the transport of electrons within the respiratory chain within the mitochondria (32), to assist mitochondrial function or even to introduce donor ooplasm to "rejuvenate" an oocyte.…”
Section: Oocyte Qualitymentioning
confidence: 99%
“…Other causes of poor egg/embryo quality beyond age-related factors include medical conditions such as type II diabetes, obesity, polycystic ovary syndrome (PCOS), as well as other genetic and environmental factors [6,7]. Over the past 25 years, an increasing body of clinical and preclinical data has demonstrated that the decline in egg quality is largely due to a reduction in energy production [8][9][10][11]. In the 1990s, there were attempts at improving egg and embryo quality by injecting cytoplasm from young, healthy, donor eggs into the eggs of women with a history of reproductive failures [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasm injection procedure involved the injection of third-party mitochondria obtained from younger donor eggs and resulted in the birth of approximately 50 seemingly healthy babies [12][13][14]. This groundbreaking work was not pursued as more study was required [11].…”
Section: Introductionmentioning
confidence: 99%